2016
DOI: 10.5222/terh.2016.207
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and etiology of postoperative chronic pain after breast surgery

Abstract: Objective: The primary aim of this study was to determine the incidence of chronic postoperative pain after the types of breast surgery. The secondary aim was to examine the factors associated with chronic postoperative pain. Methods: The prospective study included 240 female patients. Data were collected on: visual analogue scale (VAS) pain scores in the Post Anesthesia Care Unit (PACU) at 1st month and at 3rd-6th months postoperatively; and age, BMI, preoperative pain, radiotherapy, chemotherapy, postoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Contrary to all of these literature data, in our series age also plays a major role in the development of CPOP, and as age increases, the probability of chronic pain also increases. Sipila et al (12) and Turan et al (8) had similar results, namely they found a significant linear correlation between CPOP and age. Discrepancies between studies may depend on the type end extent of the operations, genetic characteristics and age of the populations, and socio-cultural differences that affect the expectations of the patients.…”
Section: Region Of Turkeysupporting
confidence: 70%
See 2 more Smart Citations
“…Contrary to all of these literature data, in our series age also plays a major role in the development of CPOP, and as age increases, the probability of chronic pain also increases. Sipila et al (12) and Turan et al (8) had similar results, namely they found a significant linear correlation between CPOP and age. Discrepancies between studies may depend on the type end extent of the operations, genetic characteristics and age of the populations, and socio-cultural differences that affect the expectations of the patients.…”
Section: Region Of Turkeysupporting
confidence: 70%
“…Most patients who experienced pain during the follow-up period were diagnosed with CPOP at the end of the second month (67 of 46; 68.7%). In our sample, we observed that the incidence of CPOP in Turkey was 14.8% when all types of (8) reported a pain incidence of 39.2% in 240 patients 3 months after breast surgery. In our study where patients with fairly even gender distribution underwent various types of surgery, the incidence of chronic pain was far lower (15%) than reported by Turan et al for their study group .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It is known that pathological types of breast tumor show different tissue invasion characteristics. [15,16] It is stated that metaplastic cancers are more aggressive compared to other types.…”
Section: Discussionmentioning
confidence: 99%